Epidemiology of ticks and tick-borne diseases in eastern, central and southern Africa. Proceedings of a workshop - Irvin, A.D.; McDermott, John J.; Perry, Brian D. (International Livestock Research Institute, 1996)
The first part of this report comprises country reports that deals with epidemiology of ticks and tick-borne diseases in Ethiopia, Kenya, Malawi, Mozambique, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe. The second part of the report covers topics on assessing the efficacy of immunization against tick-borne diseases, evaluating delivery systems for the control of tick-borne diseases and measuring the impact of immunization on livestock productivity. The paper ends with a discussion on coordination, collaboration and planning.